On the Lithuanian privative prefix ap- - Ostrowski, Norbert (Baltistica, 2024)
This paper discusses two examples of Lithuanian verbs with the privative prefix ap-, which is a continuation of the IE ablative adverb *h2épo ‘from’. The examples discussed are apgauti ‘to deceive’ and apakti ‘to go blind’. Parallels in other languages can help to establish these verbs’ original meanings: Lat. dēcipere ‘to deceive’ and Fr. aveugle ‘blind’.